Beveridge Report (Pictorial charts with explanatory notes) - Beveridge, William Henry Beveridge, Baron, 1879-1963. Social insurance and allied services
1943-01 1943 1940s 14 pages : illustrations 3. The danger which is foreseen by some people that the plan will create 'a nation of idlers' is guarded against by the fact that provision is made for training benefit to enable the unemployed men to find employment in a different type of occupation. It is interesting to note in this connection a letter to the Times by Mr. Seebohm Rowntree commenting on the Beveridge Report. He states - "The effect of the Beveridge plan is to reduce the proportion of people in poverty from 31.1 per cent. to 12.1 per cent. The following table shows the extent to which poverty arising from different causes is reduced:- Cause of Poverty. Number of persons Proportion of these in poverty. removed from poverty. % Inadequate wages. 5,643 54.5 Inadequate earnings. 1,636 26.6 Unemployment. 4,909 72.4 Old Age. 2,521 61.3 Death of husband. 1,346 72.1 Illness. 701 79.3 Miscellaneous. 429 84.8 17,185 61.1 He continues:- "Excluding the poverty of old age, 73.7 per cent. of the poverty of those receiving insurance benefits is abolished......... It may be asked why the plan does not abolish more than 73.7 per cent. of the poverty due to unemployment, death of husband, and illness. It is partly accounted for by the fact that my poverty line is a little higher than Sir William's and partly by a number of miscellaneous causes which lack of space precludes me from describing here and which cannot be dealt with by social insurance. It must, of course, not be assumed that those who are not raised above the poverty line are not better off because of the Beveridge plan. On the contrary, they are all immensely better off even though their poverty is not entirely abolished. The facts brought out above point to the conclusion that the Beveridge scheme will go a very long way towards abolishing involuntary want in the case of families receiving his proposed insurance benefits, but if the poverty due to low wages is to be abolished the enactment of an adequate statutory minimum wage is essential." (Times. 15.12.42.) Supporters and Opponents. The plan has been welcomed by the Liberal Party, the National Council of Labour (representing the Trades Union Congress, the Labour Party, and the Co-operative Union), important sections of the press and a great body of public opinion. Opposition has been indicated by the Conservative Central office in its publication the 'Onlooker', on the grounds that a decision on the plan must be deferred until the problem of the prevention of mass unemployment has been found and until we have a prosperous trade and industry to finance it. "It is only necessary to give a warning that if the 'Onlooker' reflects the opinions of Conservatives, the same tactics will be used as were used over the fuel rationing scheme....... What cannot be tolerated is sabotage, however sleek and urbane." (Economist. 16.1.43.) On the other hand the attitude of the Bishop of Bristol, Dr. C. S. Woodward, is representative of the sympathetic response which the Report has evoked from the majority of religious spokesmen: "On its first appearance the report was received with almost universal approval, but now the voices of critics and the 126/TG/377/1/1/153